2017
DOI: 10.3324/haematol.2017.163766
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of somatic mutations in monoclonal gammopathy of undetermined significance indicates a less complex genomic landscape than that in multiple myeloma

Abstract: Monoclonal gammopathy of undetermined significance is a pre-malignant precursor of multiple myeloma with a 1% risk of progression per year. Although targeted analyses have shown the presence of specific genetic abnormalities such as IGH translocations, RB1 deletion, 1q gain, hyperdiploidy or RAS gene mutations, little is known about the molecular mechanism of malignant transformation. We performed whole exome sequencing together with comparative genomic hybridization plus single nucleotide polymorphism array a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 44 publications
5
81
1
1
Order By: Relevance
“…Consequently, gene mutations are thought to be late events that contribute to MM heterogeneity and impact disease progression more than its initiation (4). In fact, NGS analysis of sample series has shown variable degrees of spontaneous evolution of genes mutations, cytogenetic lesions and mutational signatures (26)(27)(28)(29)(30)(31)(32)(33). This suggests that MM evolves in discrete steps not just clinically but also from a molecular point of view, with the acquisition of subsequent genomic lesions that underlie an increasingly aggressive clinical behavior.…”
Section: Molecular Pathogenesis Of Multiple Myeloma and Related Monocmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, gene mutations are thought to be late events that contribute to MM heterogeneity and impact disease progression more than its initiation (4). In fact, NGS analysis of sample series has shown variable degrees of spontaneous evolution of genes mutations, cytogenetic lesions and mutational signatures (26)(27)(28)(29)(30)(31)(32)(33). This suggests that MM evolves in discrete steps not just clinically but also from a molecular point of view, with the acquisition of subsequent genomic lesions that underlie an increasingly aggressive clinical behavior.…”
Section: Molecular Pathogenesis Of Multiple Myeloma and Related Monocmentioning
confidence: 99%
“…Recently, DNA and RNA-based NGS approaches applied to both individual SMM samples and paired SMM-MM cases have shown that these asymptomatic stages carry a globally lower number of mutations than NDMM (28,29). However, clonal heterogeneity was observed at this stage as well, implying spontaneous evolution of cancer cells through acquisition of new genetic lesions conferring a proliferative/survival advantage.…”
Section: Smoldering Myelomamentioning
confidence: 99%
“…By contrast, the presence of CNA was more frequent in AL amyloidosis (19/21, 90.5%; Supplementary Fig. 3) than MGUS (60.6% in Mikulasova et al) [10] and similar to MM patients (virtually 100%) [11]. Overall, these results underpin recent observations based on the immunophenotypic characterization of clonal PCs [5], and locate AL FAT4 IGLL5 MUC16 SSH2 PRK AG3 CCIN CFAP74 CKAP4 CLIC1 COL4A5 COL6A3 CSMD2 DNAH17 DNAH2 FAM135B FAM170A GABBR1 HERC1 LAMA1 LAMA3 MAGEL2 MEOX2 MORC2 MYH13 NAV1 OPCML PCDH15 PCF11 PDILT PROB1 RIMS2 SAFB SMAD1 SNAP91 SP140 VWA7 ZFHX3 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 amyloidosis in the crossroad between MGUS and MM also in genetic grounds.…”
Section: To the Editormentioning
confidence: 82%
“…Speculatively, the modulation of MAP kinase signal intensity and duration may also play a significant role in PC biology. In general, the importance of MAP kinase signaling in PC biology is suggested by the recurrent mutations of NRAS , KRAS and BRAF in myeloma (2325). While the differential signaling in ASCs consequent on such mutations remains largely unexplored, a general prediction is that these impact on the kinetics and amplitude of MAP kinase pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the signaling pathways linked to SDF1 responses in lymphocytes is activation of the MAP kinase pathway (16, 2022). Although the role of the MAP kinase pathway in normal PC biology is not defined, components of the pathway are recurrent targets of mutation in PC neoplasia including both upstream regulators such as the RAS oncogenes and downstream effector EGR1 (2325). EGR1 mutation has been reported to show a particularly high cancer clonal fraction when mutated, suggesting that it may either exert a strong selective pressure or be an early event in pathogenesis (5).…”
Section: Introductionmentioning
confidence: 99%